PENGARUH PERSEPSI KEINFORMATIFAN, HARGA, KEGUNAAN, DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT PEMBELIAN ULANG KONSUMEN GO-FOOD - Hidayat, Elrio Purnomo; Paramita, Eristia Lidia (E-Jurnal Manajemen; Vol 10 No 8 (2021)DO - 10.24843/EJMUNUD.2021.v10.i08.p05, 2021)
Technology’s rapid advancement has transformed the global economy, making it more futuristic. Companies must be dedicated to serving customers in an increasingly advanced industrial environment. The realization of repurchase intention is heavily influenced by consumer satisfaction. This study aims to describe the influence of four important perceptual factors on repurchase intention through consumer satisfaction in the Go-Food application. An online questionnaire was used to collect the data, with a total sample size of 200 respondents. The analysis technique used is   Structural Equation Modeling  (SEM). According to the results, perceived of price and perceived usefulness have a substantial effect on customer satisfaction, while perceived informativeness and perceived ease of use have no significant impact. Keywords: Perception of informativeness; Perception of Price; TAM; Consumer Satisfaction; Repurchase Intention